LABORATORY INDICATIONS OF XENOBIOTIC INFLUENCES - Hamidova Saodat Khikmatovna (Journal of new century innovations, 2023)
Abstract. The anal canal of the rat rectum is morphologically subdivided into the pre-sphincter region, the transition zone, the internal sphincter, the external sphincter, the space between the sphincters and the intersphincter zone.